Interactional Justice Moderated the Effect of Protestant Work Ethic on Social Loafing - Zhang, Suchuan; Wang, Li (Journal of Advances in Management Sciences & Information Systems, 2017)
This study examined the relationship between Protestant work ethic and social loafing and whether interactional justice was a moderator of this linkage. Responses to the survey were analyzed using a sample of 406 from Shanxi province in China. The factor analysis indicated six dimensions of PWE, that is, admiration of work itself, success comes from hard work, work as an end, asceticism, ant-leisure, and internal control. Results showed that the dimensions of “Admiration of work itself” and “Ant-leisure” related significantly to social loading and interactional justice played a moderating role in the relationship between PWE and social loafing. The limitations and directions for future research are offered finally.